Factors Affecting the Timely Construction of National Pride Projects of Nepal: A Case Study Of KTFT Road Project - Dhakal, Ashok; Pathak, Sapana (KTFT Journal, 2024)
This article provides an insight of the factors that could cause delay in the timely construction of road projects in Nepal pivoting to the Nepal’s first expressway: Kathmandu-Terai/Madhesh Fast Track Road Project. The major factors considered for the study are: geographic and environmental factors, regulatory and legal factors, socioeconomic factors, technology and innovation, finance and funding factor, political and security factor. From this research survey it is concluded that the Regulatory and Legal factors is found to be the most significant factors influencing the timely construction of the road projects in Nepal including KTFT and the least importance from the survey is determined to be the geological and environmental factor. Hence, it is recommended to focus on the Legal and Regulatory part for the concerned stakeholders in order to succeed in this type of Mega Projects in Nepal.